1981
DOI: 10.1111/j.1432-1033.1981.tb05720.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition by Sodium Butyrate of Glucorticoid‐Induced Tyrosine Aminotransferase Synthesis in Hepatoma Tissue‐Cultured Cells

Abstract: Sodium butyrate at a 5 mM concentration prevents the induction of tyrosine aminotransferase in hepatoma culture cells, without affecting the basal level of the enzyme. This effect is reversible immediately after the removal of butyrate, or after a lag, if butyrate was present for more than 2 h.Neither the amount of cellular RNA nor the rate of total RNA synthesis were affected by sodium butyrate. Furthermore butyrate does not inhibit protein synthesis : [35S]methionine incorporation into proteins, measured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Interestingly, the amplified or transfected gene is still inducible by heavy metals. Butyrate, which inhibits histone deacetylase (but also histone acetyltransferase) and alters chromatin structure, reversibly reduces the accumulation of tyrosine aminotransferase mRNA seen in response to glucocorticoids, without affecting the basal levels (Tichonicky et al, 1981). Plesko et al (1983) have shown that this short-term inhibitory effect of butyrate on transcription is specific for a few mRNA species, most of which are glucocorticoidinducible.…”
Section: Involvement Of Chromatinmentioning
confidence: 99%
“…Interestingly, the amplified or transfected gene is still inducible by heavy metals. Butyrate, which inhibits histone deacetylase (but also histone acetyltransferase) and alters chromatin structure, reversibly reduces the accumulation of tyrosine aminotransferase mRNA seen in response to glucocorticoids, without affecting the basal levels (Tichonicky et al, 1981). Plesko et al (1983) have shown that this short-term inhibitory effect of butyrate on transcription is specific for a few mRNA species, most of which are glucocorticoidinducible.…”
Section: Involvement Of Chromatinmentioning
confidence: 99%
“…Butyrate and glucocorticoids have antagonistic effects in a number of cell lines. Thus, butyrate prevents gene induction by glucocorticoids in glioma and hepatoma cells and inhibits activation by glucocorticoids of murine mammary tumor virus genes in other cells lines, whereas dexamethasone blocks the butyrate-induced differentiation of rat islet cells (2,25,32,33). Since ␣-ABA decreases the rate of globin gene switching in the hybrids, we wished to test whether glucocorticoids would have the opposite effect, i.e., acceleration of the ␥-to-␤ switch.…”
Section: Resultsmentioning
confidence: 99%
“…Butyrate and its analogs are well-established inducers or repressors of differentiation in various cellular systems (2,4,15,16,17,25,26,28,32,33). The mechanism whereby these compounds affect gene expression remains unresolved; however, it is assumed that effects on gene expression may be mediated by histone hyperacetylation because of the inhibition of histone deacetylase (17,31).…”
mentioning
confidence: 99%
“…15 In spite of its ability to activate a number of genes, such as the`dormant' fetal g-globin gene, 16 it was also noted that butyrate inhibits the transcriptional activation of several steroid hormone-dependent genes. An inhibitory effect of butyrate was shown for estrogen-mediated gene expression in the chicken oviduct, 17 for glucocorticoiddependent genes in HTC cells, 18,19 in cultured mammary gland fragments 20,21 and for thyroid-mediated gene expression in rat pituitary tumor cells. 22 Interestingly, in rat glioma C6 cells, butyrate was found to block the glucocorticoid-induced increase in glycerol phosphate dehydrogenase 23 but had no effect on glucocorticoid induction of glutamine synthase activity; 24 in HeLa cells the induction of alkaline phosphatase by dexamethasone was, however, potentiated by butyrate.…”
Section: Introductionmentioning
confidence: 99%